Software Rights: How Patent Law Transformed Software Development in America by Gerardo Con Diaz (review). - Burk, Dan L. (Technology & Culture, 2023)
Software Rights: How Patent Law Transformed Software Development in America By Gerardo Con Diaz. Much of the controversy over software patenting that Con Diaz surveys revolves around which of these categories might fit computer programs: Are they processes?.